Adeno-Associated Virus-Mediated Single-Cell Labeling of Mitral Cells in the Mouse Olfactory Bulb: Insights into the Developmental Dynamics of Dendrite Remodeling - Togashi, Kazuya; Tsuji, Masato; Takeuchi, Shunsuke; Nakahama, Ryota; Koizumi, Hiroyuki; Emoto, Kazuo (Frontiers in Cellular Neuroscience, 2020)
Neurons typically remodel axons/dendrites for functional refinement of neural circuits in the developing brain. Mitral cells in the mammalian olfactory system remodel their dendritic arbors in perinatal development, but the underlying molecular and cellular mechanisms remain elusive in part due to a lack of convenient methods to label mitral cells with single cell resolution. Here we report a novel method for single cell labeling of mouse mitral cells using adeno-associated virus (AAV)-mediated gene delivery. We first demonstrated that AAV injection into the olfactory ventricle of embryonic day 14.5 (E14.5) mice preferentially labels mitral cells in the olfactory bulb. Birthdate labeling indicated that AAV can transduce mitral cells independently of their birth dates. Furthermore, in combination with the Cre-mediated gene expression system, AAV injection allows visualization of mitral cells at single cell resolution. Using this AAV-mediated single cell labeling method, we investigated dendrite development of mitral cells and found that ~50 % of mitral cells exhibited mature dendrites with a single thick and tufted branch prior to the birth, suggesting that a certain population of mitral cells completes dendrite remodeling during embryonic stages. We also found an atypical subtype of mitral cells that have multiple dendritic shafts innervating the same glomeruli. Our data thus demonstrate that the AAV-mediated labeling method that we reported here provides an efficient way to visualize mitral cells with single cell resolution and could be utilized to study dynamic aspects as well as functions of mitral cells in olfactory circuits.